IMPROVES CRITICAL THINKING SKILLS AND SELF-EFFICACY OF LEARNERS USING THE PJBL-STEAM MODEL IN WETLAND CONTEXTS - Muhammad, Rusmansyah; Siti Awalia Rahmah; Syahmani; Mohammad Nor Aufa; Arief Ertha Kusuma; Isnawati (JCER (Journal of Chemistry Education Research), 2024)
Critical thinking skills are one of the essential thinking skills mastered in the 21st century for the progress of a nation. They can help a person to solve problems by interpreting, analyzing, evaluating, and inferring. Self-efficacy is a person's belief in his ability to solve problems. The ability to think critically is related to self-efficacy. The PjBL-STEAM model is one of the alternatives that seek to improve student’s critical thinking and self-efficacy skills. The wetland context referred to in this study uses a solution of fruits that can live in wetlands as one of the learning media on electrolyte and nonelectrolyte solution materials. This study aims to examine the improvement of critical thinking and self-efficacy of students through the use of the PjBL-STEAM learning model in wetland contexts by comparing pretest and posttest values. This research model is quasi-experimental with a one-group pretest-postest research design. This study was conducted at SMAN 3 Barabai with a study population of class X MIA, and the sample taken purposively was 25 students of class X MIA 3. Data collection using tests and questionnaires. Data analysis was carried out by comparing pretest and posttest values. The results showed that the PjBL-STEAM learning model in the wetland context could improve the critical thinking skills and self-efficacy of students with an N-gain value of critical thinking ability of 0.58 (moderate category) and N-gain self-efficacy of 0.75 (high category). In other words, using PjBL-STEAM in wetland contexts is stated to be effective for improving students' critical thinking skills and self-efficacy.